2003
DOI: 10.1002/cne.10757
|View full text |Cite
|
Sign up to set email alerts
|

Connections of the retrosplenial granular b cortex in the rat

Abstract: Although the retrosplenial granular b cortex (Rgb) is situated in a critical position between the hippocampal formation and the neocortex, surprisingly few studies have examined its connections carefully. The present experiments use both anterograde and retrograde tracing techniques to characterize the connections of Rgb. The main cortical projections from Rgb are to the caudal part of the anterior cingulate cortex, area 18b, retrosplenial granular a cortex (Rga), and postsubiculum, and less dense terminal fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
329
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(352 citation statements)
references
References 82 publications
22
329
0
1
Order By: Relevance
“…Lu et al (2012) demonstrated in rats that the default-mode network not only exists but also includes homologues of key structures noted in our work and that of others (Poppenk and Moscovitch, 2011) (eg, anterior cingulate cortex, retrosplenial cortex, and the dorsal hippocampus), which further strengthens the basis for parcellating hippocampus along its longitudinal axis. As such, converging evidence from noninvasive neuroimaging methods, along with those based on comparative anatomy techniques (ie, tract tracing) in rats (Van Groen and Wyss, 2003) and monkeys (Aggleton et al, 2012;Roberts et al, 2007), together provide support for the homology of hippocampal subdivisions that are the basis for this study (dorsal/ventral and posterior/anterior, respectively).…”
Section: A Default-mode Network-based Posterior Hippocampus Circuitrymentioning
confidence: 65%
“…Lu et al (2012) demonstrated in rats that the default-mode network not only exists but also includes homologues of key structures noted in our work and that of others (Poppenk and Moscovitch, 2011) (eg, anterior cingulate cortex, retrosplenial cortex, and the dorsal hippocampus), which further strengthens the basis for parcellating hippocampus along its longitudinal axis. As such, converging evidence from noninvasive neuroimaging methods, along with those based on comparative anatomy techniques (ie, tract tracing) in rats (Van Groen and Wyss, 2003) and monkeys (Aggleton et al, 2012;Roberts et al, 2007), together provide support for the homology of hippocampal subdivisions that are the basis for this study (dorsal/ventral and posterior/anterior, respectively).…”
Section: A Default-mode Network-based Posterior Hippocampus Circuitrymentioning
confidence: 65%
“…A simpler patchwork model is based on the evolutionary addition of visual areas depending on the species' visual ability (de Haan and Cowey, 2011). The rodent area PM, located between V1 and the retrosplenial cortex, has been shown to mediate visually evoked activity between these areas (Van Groen and Wyss, 2003;Xu et al, 2007). The retrosplenial complex receives projections from medial visual areas, further projects to the hippocampus (Wyss and Van Groen, 1992), and is involved in observing familiar environments (Vann et al, 2009).…”
Section: Functional Role Of Pmmentioning
confidence: 99%
“…The visual information required for navigation is projected from visual cortex via retrosplenial cortex to the hippocampus (Wyss and Van Groen, 1992;Vann et al, 2009). In rodents, the retrosplenial cortex receives this information from the medial secondary visual area (Van Groen and Wyss, 2003), which has been described to be identical to the location of PM (Wang and Burkhalter, 2007). In addition, voltage-sensitive dye imaging has shown that visual stimulation evokes activity waves originating in V1 and traveling toward PM from where feedback waves are returned (Xu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Both regions are thought to be affected in schizophrenia (Morris et al 2005;Bluhm et al 2009) and connected to the PFC (Van Groen and Wyss, 2003;Price, 2007). Previous studies have shown that PCP administration increases the c-Fos mRNA expression in both glutamatergic and GAD67 positive neurons in the RS and in GAD67 positive neurons in the CA1 (Kargieman et al 2007;Santana et al 2011).…”
Section: Pcp-induced C-fos-ir In Gabaergic Interneuronsmentioning
confidence: 99%